MU’TEZİLE’NİN TARİH ALGISI - Osman Aydınlı (İslami İlimler Dergisi)
In the history of Islamic thought, the Mu’tazilite school is characterized by its particular method in understanding religion and religious tradition and by its rational attribution to Islamic precepts. First of all, Mu’tazilite theologians laid down their principles as ‘al-usûl al-khamsah (five root and fundamentals) and focused on theological and philosophical issues. In the view of its environment where it’s been developed, its justification for historical events and its comprehension of leadership, the school has been divided into two parts which are Basrian Mu’tazilite and Bagdadian Mu’tazilite. Choice of the ancestry of Ali, the assumed attitude to the current political structure, comprehension of history and compromising with the society were the important reasons of the separation. Mu’tazilite has been opposed to the idea of idealizing and dignifying the past which can be seen especially in Shiite, by historical criticizing and analytical mentality. Meanwhile, the school did not ignore to be compatible with the history and the society. Mu’tazilite has emphasized the need of describing the history as what it is and displaying it with all diversities and contradictions. The experiences of Mu’tazilite of coming to power, being suspended from the power and being integrated with the other religious affinities have shaped their historical perspectives. These experiences have shaped their historical perspective. In this article, we tried to determine the Mu’tazilite’s perception of history by taking into consideration its evolutions in period.